Avaliação da atividade antimicrobiana dos extratos brutos das espécies vegetais Miconia rubiginosa e Pfaffia glomerata em microrganismos da cavidade bucal - Moura, Cláudia Lemos (2006)
Studies on the biological activity of extracts and substances isolated from species of the genus Miconia have shown significant results, such as trypanocidal, analgesic, antifungal, antitumor and antimicrobial activity. Still in Brazil, several species of the genus Pfaffia, family Amaranthaceae, are used to replace ginseng, being known as "Brazilian ginseng" and fáfia, where the species are: Pfaffia glomerata, Pfaffia eresinoides and Pfaffia paniculata. Among the activities already evaluated for Pfaffia species, the following stand out: antitumor activity; analgesic; trypanocidal; anti-inflammatory; stimulating effect on the sexual performance of male rats; depressive activity of the central nervous system and amnesic effect. To date, there are no studies on these plants relating them to antimicrobial activity against microorganisms in the oral cavity. This work aimed to verify the antimicrobial activity of crude extracts of Miconia rubiginosa and Pfaffia glomerata in oral cavity microorganisms by the agar diffusion method and by the broth dilution method to determine the Minimum Inhibitory Concentration. Hexanic, dichloromethane and ethanolic extracts of M. rubiginosa and ethanolic extracts of P. glomerata were used. Chlorhexidine Digluconate was used as a positive control. For statistical analysis, the ONE-WAY ANOVA test was used for the agar diffusion method and to compare the averages between the concentrations, the Tukey test was used. The results demonstrated, by the agar diffusion method, that all extracts showed antimicrobial activity in most of the evaluated microorganisms, and the averages of the inhibition halos ranged from 8.33 mm to 22.67 mm. By the broth dilution method, the extracts showed antimicrobial activity with an MIC that ranged from 60 to 300 µg / mL. The antimicrobial action observed in the extracts suggests its use as an adjuvant in the control of dental caries.